Ghosts don't wear glasses - Farber, Erica (Fish Finelli, 2015)
In order to fulfill a bet with Bryce, his nemesis, Fish has to go into the Hannibal W. Royce house, which is said to be haunted by the ghost of a whaling captain, and bring out the whaler's harpoon, which is supposedly dripping with blood.